Computational fluid–structure interaction analysis of blood flow on patient-specific reconstructed aortic anatomy and aneurysm treatment with Dacron graft. (August 2018) - Jayendiran, Raja; Nour, Bakr; Ruimi, Annie
Abstract: We use the fluid–structure interaction (FSI) capability in Abaqus to evaluate radial displacements, von Mises stresses and wall shear stresses (WSS) on the human aorta in response to the blood flowing through it. Complications arise when aneurysm is detected and causes the wall to thinner so much that rupture may result. We use the Materialise suite, a specialty software to reconstruct a three-dimensional geometry of the aorta from two-dimensional computerized axial tomography (CAT) images. Results are compared to those obtained on a healthy individual. Blood is assumed to be a Newtonian and incompressible medium and the blood flow is taken as pulsatile, fully developed and turbulent. The model used for aorta is Holzapfel–Gasser–Ogden (HGO), a sophisticated hyperelastic model that can describe biological tissues. We also study the behavior of Dacron, a polyester fabric used as graft in aortic surgical repair. Here, Dacron is represented by a neo-Hookean (isotropic) hyperelastic model. Time-dependent pressure conditions are assumed at the inlet and outlet of the resulting structure. Results indicate that using a patient-specific geometry for the aorta yields additional insight on the state of the stresses applied on the aortic walls. In addition, stress contours on the Dacron are comparable to those obtained on a healthy patient and stresses evaluated at the interface of the biological tissues and the fabric, provide useful information regarding the suture strength needed during surgery. In the case of aneurysm, our simulation results agree well with experimental data taken from the literature particularly with regard to WSS which can be used to assess the seriousness of the aneurysm condition. If an idealized cylindrical shell is used in place of the reconstructed anatomy, the von Mises stress values do not differ much but it underestimates the values of WSS which could interpreted as the presence of an aneurysm when there is not. Among the novel contributions, the present FSI model has the ability to predict the Dacron's response to realistic hemodynamic loading conditions.